Density Functional Theory (dft) Calculations, Synthesis And Electronic Properties Of Alkoxylated-chalcone Additive In Enhancing The Performance Of Cmc-based Solid Biopolymer Electrolyte - Wan M. Khairul; Rafizah Rahamathullah; Janice Roria Joni; Mohd Ikmar Nizam Mohamad Isa (Elsevier, 2024)
Indexed by WOS/SCOPUS/ERA